Pengembangan bahan ajar digital Geografi berbasis STEM-E pada materi pengelolaan sumber daya alam Indonesia - Dya Wahyu Kusumaningtyas; Budi Handoyo; Fatiya Rosyida; Djoko Soelistijo (Universitas Negeri Malang, 2023)
The need for teaching materials in 21st century learning leads to the use of technology, information and digital media. The right geography learning method in the 21st century with a learning approach based on STEM-E (Science, Technology, Engineering, Mathematics, and Ecology). The purpose of this study was to develop digital Geography teaching materials based on STEM-E (Science, Technology, Engineering, Mathematics, and Ecology) in Indonesian natural resource management materials. The development of digital teaching materials is carried out using the ADD model. The feasibility of digital teaching materials is obtained from the results of validation carried out by material, media, and language experts using validation instruments. The subjects of the feasibility test for digital teaching materials were students of class XI IPS 1 and a teacher of Geography conducted at SMAN 5 Malang. The results of the feasibility of the validation and the test subjects were analyzed using a descriptive percentage technique. The results of the validation of material, media, and language experts obtained a total percentage of 94.33 percent. The results of the feasibility test on teachers and students obtained an average percentage of 76 percent and 88 percent, respectively. Based on the results of the study, the STEM-E-based digital Geography teaching materials on Indonesian natural resource management materials were declared suitable for use by class XI high school students. Kebutuhan bahan ajar pada pembelajaran abad 21 mengarah pada pemanfaatan teknologi, informasi dan media digital. Metode pembelajaran Geografi yang tepat pada abad 21 dengan pendekatan pembelajaran berbasis STEM-E. Tujuan penelitian ini dilakukan untuk menghasilkan bahan ajar digital Geografi berbasis STEM-E (Science, Technology, Engineering, Mathematics, and Ecology) pada materi pengelolaan sumber daya alam Indonesia. Pengembangan bahan ajar digital dilakukan menggunakan model ADD. Kelayakan bahan ajar digital diperoleh dari hasil validasi yang dilakukan oleh ahli materi, media, dan bahasa dengan menggunakan instrumen validasi. Subjek uji kelayakan bahan ajar digital adalah peserta didik kelas XI IPS 1 dan guru Geografi dilakukan di SMAN 5 Malang. Hasil kelayakan validasi dan subjek uji coba dianalisis menggunakan teknik deskriptif persentase. Hasil validasi ahli materi, media, dan bahasa memperoleh jumlah persentase 94,33 persen. Hasil uji kelayakan pada guru dan peserta didik memperoleh rata-rata persentase 76 persen dan 88 persen. Berdasarkan hasil penelitian tersebut, bahan ajar digital Geografi berbasis STEM-E pada materi pengelolaan sumber daya alam Indonesia dinyatakan layak digunakan peserta didik kelas XI SMA.